Innovative Concepts for Alternative Migration Policies Ten Innovative Approaches to the Challenges of Migration in the 21st Century - Jandl, Michael; Jandl, Michael (Amsterdam University Press, 2007)
This book is directed at researchers and policymakers at all levels and is intended to stimulate fresh thinking for the development of unconventional and innovative ideas for migration policymaking. The papers in this edited volume are the results of a joint ICMPD/IMISCOE workshop on Innovative Concepts for Alternative Migration Policies, held at the International Centre for Migration Policy Development in Vienna in 2006, with the participation of migration researchers, policymakers and representatives of international organisations. Based on the strengths of the combined ideas presented by the authors of these ten short papers, eight basic principles for the design of innovative migration policy approaches are presented and developed. This title is available in the OAPEN Library - http://www.oapen.org.
English
Keywords: Politics & government; Comparative politics; Sociology; Politics and government; Comparative politics; Sociology; Political Science; Sociology